Normative Perspective and Rational Perspective in the Expansion of Nagari-Nagari in West Pasaman Regency - Nahdatun Nisa Mubai; Dede Sri Kartini; Novie Indrawati Sagita (Universitas KH. Abdul Chalim Mojokerto, 2024)
Policy transformation regarding regional expansion is an issue that has attracted quite a lot of attention, especially in the context of local government such as villages in West Pasaman Regency. The expansion of villages that occurred during the period 2017 to 2023 is a relevant object of study to be examined from two main approaches, namely the normative perspective and the rational perspective. The normative perspective focuses on the suitability of the implementation of expansion with applicable laws and regulations, while the rational perspective emphasizes logical considerations, governance efficiency, and real benefits for the community. This study uses a descriptive method with a qualitative approach, which aims to describe in depth the dynamics of the implementation of village expansion. Data collection techniques were carried out through literature studies, direct observations in the field, policy documentation, and interviews with a number of key informants from the Community Empowerment and Village Office of West Pasaman Regency, Muaro Village officials, Ranah Koto Tinggi Village officials, and community leaders from both villages. Data analysis was carried out through the stages of data collection, reduction, data presentation, verification, and drawing conclusions. The results of the study indicate that from the normative side, the expansion has been running according to formal provisions, although there are still implementation obstacles at the local level. Meanwhile, from the rational side, the expansion has not been fully able to present optimal impacts as planned in several aspects.